Плоская несимметричная задача ударного взаимодействия твердого эллиптического цилиндра с жидкостью - Кубенко, В.Д.; Гавриленко, В.В. (Нелінійні коливання, 1999)
Розглядається плоска несиметрична задача вертикального удару твердого елiптичного цилiндра по поверхнi стисливої рiдини. Розв’язок крайової задачi зводиться до розв’язку нескiнченної системи лiнiйних iнтегральних рiвнянь Вольтерра другого роду. В чисельному прикладi проведено аналiз результатiв для рiзних значень початкового кута асиметрiї. Planar asymmetrical problem of impact of rigid body into a compressible fluid is considerated. It is supposed thet the penetrating elliptical cylindrical body has biased center of mass. Solution of the boundary problem is redused to infinite system of 2-nd kind Volterra’s integral equations. An analysis of results as a function of initial means of angle of asymmetry is done.